(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2019)
Hanging and Strangulation are amongst the commonest mode of Asphyxial deaths. Usually deaths due to hanging are suicidal and those due to strangulation are homicidal in nature. This study was conducted in department of Forensic Medicine and Toxicology, Moti Lal Nehru Medical College Allahabad. The present study was conducted between 1st May 2016 to 30th April 2017, for cases of Asphyxial deaths coming for medico legal post mortem at mortuary of Swaroop Rani Nehru hospital Allahabad are examined. Cases of Hanging are more common in either sex in comparison with strangulation as in Table 1 and Figure 1a and 1b. Majority of victims of both Hanging (55%) and Strangulation (13.33%) were of age group 21-40 years as in Table 2 and Figure 2a and 2b. Out of 94 cases of hanging suicide accounts for maximum in 92(76.66%) while out of 26 cases of strangulation homicidal cases are maximum 25(20.85%). In majority of cases the place of incidence was inside home 88 (73.33%) and outside home 12(10%) respectively. Cases of hanging and strangulation has been taken place most commonly in 45 (37.5%) during 6 -12 pm and 8(6.6%) during 12-6 am respectively.